2015
DOI: 10.1684/agr.2015.0771
|View full text |Cite
|
Sign up to set email alerts
|

Difficult access to advisory services for small farms : the situation in Mayotte

Abstract: Le conseil en agriculture est perçu par les acteurs du développement agricole comme étant important pour l'amélioration des performances des exploitations. Cependant, seules certaines catégories d'exploitation accèdent au conseil que ce soit dans les pays du Sud ou dans ceux du Nord où dominent les petites exploitations familiales. L'objectif de l'article est de caractériser les déterminants de l'accès au conseil des petites exploitations dans les départements d'outre-mer français en abordant le cas de Mayotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This is in line with the work of Birner et al (2009) and Bruce (2019). These results also show that agro-suppliers disseminate conventional practices, with little consideration of environmental issues, despite the expectations of some farmers, especially small family farms, as observed by other authors in Algeria (Ouendeno et al, 2015) or elsewhere Rebuffel, 2015;Bekkar et al, 2015).…”
Section: Neglect Of Small Farms By Agro-suppliers: a Blessing In Disg...supporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with the work of Birner et al (2009) and Bruce (2019). These results also show that agro-suppliers disseminate conventional practices, with little consideration of environmental issues, despite the expectations of some farmers, especially small family farms, as observed by other authors in Algeria (Ouendeno et al, 2015) or elsewhere Rebuffel, 2015;Bekkar et al, 2015).…”
Section: Neglect Of Small Farms By Agro-suppliers: a Blessing In Disg...supporting
confidence: 90%
“…This trend is particularly prevalent in developing countries, where institutional arrangements between public farm advisory systems and private companies enable the latter to guide the decisions of agricultural producers and disseminate practices that align with their commercial interests (Compagnone et al, 2015). This has led to the emergence and extension of the intensive production model, particularly in certain so-called high value-added agricultural sectors (Rebuffel et al, 2015). It has also led to the mobilization of the various actors in the institutional environment around the promotion of this model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dominik et al [17] showed that farmers would participate in agricultural extension only if the services and information they demanded were specifically recommended and answered. Rebuffel et al [18] studied French farmers and found that local advisory services supply only a small proportion of the population while neglecting to reach out to other different types of farmers.…”
Section: Introductionmentioning
confidence: 99%